Pt-single atom decorated TiO2: Tuning anodic TiO2 nanotube structure and geometry toward a high-performance photocatalytic H2 production - Chen, Xuewen; Qin, Shanshan; Denisov, Nikita; Kure-Chu, Song Zhu; Schmuki, Patrik (Electrochimica Acta, 2023)
Atomically dispersed Pt single atoms (SAs) on titania have been reported to be a highly effective co-catalyst in photocatalytic H2 generation. In this report, we grew layers of anodic TiO2 nanotubes (NTs) varying the lengths of the NTs from 1 to 18 μm as well as their crystalline state by thermal annealing over a wide range of temperatures (350 °C – 800 °C). We then decorated the nanotubes with single atom (SA) Pt co-catalysts deposited from H2PtCl6 solutions with various concentrations of 0.001–2 mM Pt and evaluate the photocatalytic H2 generation performance for the different NT layers under UV and solar illumination. The highest photocatalytic performance is achieved for 15–18 μm long anatase NTs decorated with Pt SAs from a 0.01 mM H2PtCl6 solution (leading to a Pt SA surface concentration of 5.6 × 105 /µm2). Except for a sufficient SA Pt loading and an anatase structure, the key parameter is the photon absorption length for near-band-gap UV and AM 1.5 light. Such optimized Pt SA@TiO2 NTs show a most efficient H2, outperforming many other photocatalytic 3D titania structures, such as titania-based powders, flakes, and Metal–Organic Frameworks (MOFs) tested under the same illumination conditions.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Photocatalytic H; Pt single atoms; TiO; TiO; TiO